Construction of porous N-doped graphene layer for efficient oxygen reduction reaction. (2nd February 2019) - Chen, Xiaofang; Liang, Yan; Wan, Li; Xie, Zongli; Easton, Christopher D.; Bourgeois, Laure; Wang, Ziyu; Bao, Qiaoliang; Zhu, Yonggang; Tao, Shanwen; Wang, Huanting
Graphical abstract: Highlights: Conversion of chitosan into microporous N-doped graphene on thermally removable g-C3 N4 . Microporous N-doped graphene had high surface area and nitrogen doping level. Microporous N-doped graphene exhibited better performance than Pt/C for ORR. Abstract: Graphitic carbon materials have shown great potential for use as high-performance catalysts for electrochemical reactions and devices. In this work, we developed a simple and versatile method for synthesis of porous N-doped graphene layers (NGS) by high-temperature treatment of chitosan film deposited on the graphitic carbon nitride (g-C3 N4 ) nanosheets. In the sandwiched chitosan/g-C3 N4 /chitosan structure, the g-C3 N4 nanosheet served as a substrate for chitosan film. The pyrolysis of this substrate, g-C3 N4 nanosheet, prevented the severe agglomeration of as-carbonized chitosan sheets and resulted the porous structure. The BET surface area, micropore volume, nitrogen content and graphitic level of result sample highly depended on the heat-treatment temperature. The NGS synthesized at 1000 °C (NGS-1000) exhibited an ultrahigh specific surface area (1183 m 2  g −1 ) and high nitrogen content (4.12%). Importantly, NGS-1000 exhibited a higher limiting current density (5.8 mA cm −2 ) and a greater stability than the commercial Pt/C electrocatalyst in alkaline media for oxygen reduction reaction (ORR). Such excellent electrocatalytic performance can be explained by a balanced combination of appropriate nitrogen doping level, the degree of graphitization, porous structure, and high specific surface area.